Carbon nanotube dispersion and conductive material using same

By adding dispersant and binder components to the carbon nanotube dispersion, the connecting structure of the carbon nanotube aggregate is formed, and the problem of insufficient conductivity of carbon nanotubes in the prior art is solved, and a high-conductivity carbon nanotube dispersion and materials are realized.

CN119547161APending Publication Date: 2025-02-28KUSUMOTO CHEM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380053866.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-08-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, even if the carbon nanotubes are evenly dispersed, the conductivity will not increase accordingly, mainly because the amount of the carbon nanotubes cannot be too much, resulting in the inability to form the conductive paths between the carbon nanotubes.

Method used

By adding dispersant and binder components to the carbon nanotube dispersion, a structure in which a plurality of carbon nanotube aggregates are connected to each other is formed, thereby achieving the formation of conductive paths. Even if the amount of the carbon nanotubes is a small amount, it can impart high conductivity.

Benefits of technology

It is realized that even if the carbon nanotube blending amount is small, it can impart high conductivity, forming a carbon nanotube dispersion and a conductive material with high conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547161A_ABST
    Figure CN119547161A_ABST
Patent Text Reader

Abstract

Provided are: a carbon nanotube dispersion which is capable of imparting high conductivity even when the amount of carbon nanotubes blended is small; and a conductive material which uses the carbon nanotube dispersion. This carbon nanotube dispersion contains carbon nanotubes, a dispersant, and a binder component. The carbon nanotubes are preferably single-layer carbon nanotubes. The adhesive component is preferably an acrylic resin. The conductive material according to the present invention contains the carbon nanotube dispersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon nanotube dispersion and a conductive material using the carbon nanotube dispersion. Background Art

[0002] Carbon nanotubes are known as materials with great industrial expectations due to their unique surface area, aspect ratio, and properties as conductors, and various research papers have reported on their applications in electrical, electronic, chemical, and engineering fields since their discovery.

[0003] Patent Document 1 describes a dispersion containing a dispersion medium, metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt, and single-walled carbon nanotubes as a dispersion capable of producing a composite having high conductivity with a low single-walled carbon nanotube content.

[0004] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2021-57271 Summary of the invention Problems to be solved by the invention However, even if the carbon nanotubes (especially single-walled carbon nanotubes) are uniformly dispersed, the conductivity does not increase accordingly. This is believed to be because, from the perspective of dispersibility and cost issues, the amount of carbon nanotubes cannot be too much, and it is difficult to form a conductive path in which the carbon nanotubes are connected to each other. In other words, if a structure in which a plurality of carbon nanotubes are appropriately assembled and connected to each other is formed, a conductive path can be formed, so it is believed that even if the amount of carbon nanotubes is small, a high conductivity can be exhibited.

[0005] Therefore, an object of the present invention is to provide a carbon nanotube dispersion capable of imparting high electrical conductivity even when the blending amount of carbon nanotubes is small, and a conductive material using the carbon nanotube dispersion.

[0006] Means for solving problems The carbon nanotube dispersion of the present invention comprises carbon nanotubes, a dispersant and a binder component.

[0007] The conductive material of the present invention includes the above-mentioned carbon nanotube dispersion.

[0008] Effects of the Invention According to the present invention, it is possible to provide a carbon nanotube dispersion capable of imparting high electrical conductivity even when the blending amount of carbon nanotubes is small, and a conductive material using the carbon nanotube dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1This is a microscope photograph showing the state of structured carbon nanotubes in the carbon nanotube dispersion of the present invention. DETAILED DESCRIPTION

[0010] The carbon nanotube dispersion of the present invention comprises carbon nanotubes, a dispersant and a binder component. In the carbon nanotube dispersion, Figure 1 As shown in the microscope photograph, a structure is formed in which a plurality of carbon nanotubes are aggregated and connected to each other, so that even if the amount of carbon nanotubes blended is small, high conductivity can be imparted.

[0011] Carbon nanotubes (CNTs) have a structure in which a sheet (graphene sheet) on a plane made of carbon is rolled into a tube. They can be single-layer carbon nanotubes (SWCNTs) in which one layer of graphene sheets is coaxially tube-shaped, or multilayer carbon nanotubes (MWCNTs) in which two or three layers of graphene sheets are coaxially tube-shaped. Among them, single-layer carbon nanotubes are preferred in terms of being able to expect higher conductivity even if the amount is small. Carbon nanotubes can be used alone or in combination of two or more.

[0012] Dispersants are components that disperse carbon nanotubes in a binder resin to easily form a structure formed by interconnecting aggregates of a plurality of carbon nanotubes. Dispersants include, in addition to surfactants such as anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants, polymeric dispersants other than surfactants can also be cited. Dispersants can be used alone or in combination of two or more.

[0013] As anionic surfactants, carboxylic acid-type anionic surfactants such as aliphatic carboxylic acids, aromatic carboxylic acids, polyether carboxylic acids and their salts can be listed; sulfonic acid-type anionic surfactants such as aliphatic sulfonic acids, aromatic sulfonic acids and their salts; sulfate-type anionic surfactants such as alkyl sulfates, polyether sulfates, oil sulfates and their salts; phosphate-type anionic surfactants such as alkyl phosphates and their salts, polyether phosphates and their salts, alkyl polyether phosphates and their salts. Among them, from the perspective of the dispersibility of CNTs and the compatibility with the binder resin, phosphate-type anionic surfactants are preferred, and polyether phosphates or alkyl polyether phosphates or their salts are more preferred. As counterions of anionic surfactants, alkali metal ions such as lithium ions, sodium ions, and potassium ions can be listed; alkaline earth metal ions such as calcium ions, strontium ions, and barium ions. Anionic surfactants can be used alone or in combination of two or more.

[0014] Examples of cationic surfactants include ammonium salt-type cationic surfactants such as alkyltrimethylammonium salts and dialkyldimethylammonium salts; and amine-type cationic surfactants such as alkylamines, dialkylamines, trialkylamines, polyetheramines, and salts thereof. Among them, from the perspective of the dispersibility of CNTs and the compatibility with the binder resin, amine-type cationic surfactants are preferred, and polyetheramines or their salts are more preferred. Examples of counterions of cationic surfactants include fluoride ions, chloride ions, bromide ions, iodide ions, and the like. Cationic surfactants can be used alone or in combination of two or more.

[0015] As nonionic surfactants, ester-type nonionic surfactants such as glycol fatty acid esters, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, and polyglycerol fatty acid esters can be listed; ether-type nonionic surfactants such as polyoxyalkylene alkyl ethers and polyoxyalkylene alkylphenyl ethers; ester-ether nonionic surfactants such as polyoxyalkylene fatty acid esters; polyalkylene glycol-type nonionic surfactants such as polyoxyalkylene and its derivatives. Among them, from the perspective of the dispersibility of CNTs and the compatibility with the binder resin, polyalkylene glycol-type nonionic surfactants are preferred, and polyoxyalkylene is more preferred. As polyoxyalkylene, polyoxyethylene-polyoxypropylene condensates can be listed. The nonionic surfactant can be used alone or in combination of two or more.

[0016] Examples of the amphoteric surfactant include carboxybetaine-type amphoteric surfactants such as alkyl betaine and aliphatic amide alkyl betaine. The amphoteric surfactant can be used alone or in combination of two or more.

[0017] Examples of the polymer dispersant that can be used as the dispersant include polyvinyl alcohol and polyvinyl pyrrolidone.

[0018] The number average molecular weight (Mn) of the dispersant is preferably 300 to 50,000, more preferably 500 to 3,000, from the viewpoint of compatibility with the binder resin and dispersibility of CNTs.

[0019] The binder component is a component that disperses the carbon nanotubes and forms a matrix of a structure in which a plurality of carbon nanotubes are aggregated and connected to each other. Examples of the binder component include thermosetting resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, alicyclic epoxy resin, phenol-formaldehyde resin, melamine resin, unsaturated polyester resin, alkyd resin, silicone resin, polyurethane, and polyimide; polyethylene, polypropylene, polyolefin, polyvinyl chloride, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl acetal, polyvinyl butyral, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, and acrylonitrile. Thermoplastic resins such as butadiene styrene, acrylic resins (polyacrylates, polymethacrylates), polyamides, polyacetals, polycarbonates, polyesters, polyphenylene sulfide, polysulfones, polyethersulfones, liquid crystal polymers, polyetheretherketones, thermoplastic polyimides, and polyamideimides; liquid polymers such as silicone oils, polyalkylene glycols, polyethylene glycols, polycarbonate polyols, polyester polyols, and polyether polyols; binder resins such as elastomers such as silicone resins, unvulcanized rubbers, and thermoplastic elastomers. Among them, acrylic resins (acrylic polymers) are preferred from the viewpoint of compatibility with the dispersant. The binder component can be used alone or in combination of two or more.

[0020] Examples of the monomers forming the acrylic resin include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, and 2-ethylhexyl methacrylate; nitrile compounds such as acrylonitrile and methacrylonitrile; acrylic oligomers such as methoxypolyethylene glycol monoacrylate, methoxypolypropylene glycol monoacrylate, methoxypolyethylene glycol monomethacrylate, methoxypolypropylene glycol monomethacrylate, polyoxyalkylene acrylate, and polyoxyalkylene methacrylate. The monomers forming the acrylic resin may be used alone or in combination of two or more.

[0021] The weight average molecular weight (Mw) of the binder component is preferably 1,000 to 300,000, more preferably 1,000 to 20,000, from the viewpoint of processability during dispersion production.

[0022] The solubility parameter (SP) of the binder component is preferably 6 to 12, more preferably 8 to 10, from the viewpoint of compatibility with the dispersant, but varies greatly depending on the types of the dispersant and solvent used in combination.

[0023] The content of carbon nanotubes in the carbon nanotube dispersion of the present invention can be appropriately adjusted to achieve the desired conductivity, but is preferably 0.01 to 20% by weight. A carbon nanotube content of 0.01% by weight or more can impart higher conductivity. A carbon nanotube content of 20% by weight or less can achieve good dispersibility. The carbon nanotube content is more preferably 0.1 to 10% by weight, further preferably 0.3 to 5% by weight, and particularly preferably 0.5 to 2% by weight.

[0024] The weight ratio of the dispersant to the binder component in the carbon nanotube dispersion of the present invention (dispersant / binder component) can be appropriately adjusted to achieve the desired conductivity, but is preferably 1 / 99 to 99 / 1. By setting the weight ratio of the dispersant to the binder component to the above range, a higher conductivity can be imparted. The weight ratio of the dispersant to the binder component (dispersant / binder component) is more preferably 3 / 97 to 90 / 10, further preferably 5 / 95 to 50 / 50, and particularly preferably 7 / 93 to 20 / 80.

[0025] The carbon nanotube dispersion of the present invention may also contain a solvent. Examples of the solvent include: water; aliphatic hydrocarbons such as n-hexane and n-heptane; aromatic hydrocarbons such as toluene, o-xylene, m-xylene, and p-xylene; alcohols such as methanol, ethanol, propanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as ether and tetrahydrofuran; esters such as ethyl acetate, propyl acetate, butyl acetate, and ethyl propionate; halogenated hydrocarbons such as dichloromethane and chloroform; glycol ethers such as ethylene glycol n-butyl ether, diethylene glycol n-butyl ether, and propylene glycol monomethyl ether acetate, and their derivatives. The solvent may be used alone or in combination of two or more.

[0026] The carbon nanotube dispersion of the present invention may also contain other components other than the above-mentioned components according to the purpose. Other components include: preservatives, viscosity adjusters, surface adjusters, defoamers, pH adjusters, rust inhibitors, lubricants, anti-aging agents, antibacterial agents, flame retardants, ultraviolet absorbers, mold release agents, antistatic agents, dyes, pigments, inorganic microparticles other than carbon nanotubes, and organic microparticles. Other components can be used alone or in combination of two or more.

[0027] The carbon nanotube dispersion of the present invention can be manufactured by mixing carbon nanotubes, dispersants, and adhesive components. These three components can also be mixed in one stage or multiple stages in consideration of the processability of the raw materials and the dispersibility of the carbon nanotubes. In the case of a mixed solvent or other components, the timing is arbitrary. As a stirrer for mixing, for example, a high-speed stirrer, a homogenizer, a planetary mixer, a self-rotating revolution mixer, a roller mill, a wet mill, a colloid mill, a bead mill, a grinder, a ball mill, an ultrasonic disperser, a high-pressure disperser, a static mixer, a kneader, a Banbury mixer, or an extruder can be used.

[0028] The carbon nanotube dispersion as described above can impart high conductivity even when the amount of carbon nanotubes added is small, so a conductive material containing the carbon nanotube dispersion can be formed. The conductive material includes functional materials such as a conductivity imparting agent, an antistatic agent, and an electromagnetic wave shielding agent, and its uses include materials for batteries, materials for electronic components, materials for coatings, and materials for inks.

[0029] <Example> <Example 1> A carbon nanotube dispersion was prepared by mixing 1 part by weight of single-walled carbon nanotubes (SWCNT, manufactured by OCSiAl, trade name: TUBALL 01RW03), 4 parts by weight of polyether phosphate (PEP, Mn=2000, HLB=2) as a dispersant, and 95 parts by weight of acrylic resin (poly(butyl acrylate / isobutyl acrylate), PBA / PIBA, Mw=16000, SP=8.9) as a binder component.

[0030] 1.26 parts by weight of carbon nanotube dispersion was added to a mixture of 90 parts by weight of acrylic resin (DIC, trade name: ACRYDIC WL-421) with a resin solid content of 50% by weight and 10 parts by weight of butyl acetate, and the mixture was stirred and mixed at 2500 rpm × 10 min using a dissolver with a 40 mm blade to obtain a carbon nanotube dispersion. Butyl acetate was added to dilute the obtained carbon nanotube dispersion so that the viscosity of the obtained carbon nanotube dispersion at 60 rpm (measurement temperature: 25°C) based on a B-type viscometer was about 700 mPa・s, and the viscosity of the obtained carbon nanotube diluted dispersion at 60 rpm and 6 rpm (measurement temperature: 25°C) was measured, and the thixotropic index (T.I. value, 6 rpm viscosity / 60 rpm viscosity) was calculated. In addition, the carbon nanotube diluted dispersion was applied to a glass plate using a 100 μm applicator and dried naturally to obtain a coating film, and the surface resistivity of the coating film was measured using a surface resistivity meter (manufactured by Simco Japan, trade name: Worksurface Tester ST-4). The evaluation results (T.I. value and surface resistivity) are shown in Table 1.

[0031] <Examples 2 to 8, Comparative Examples 1 to 3> A carbon nanotube dispersion was prepared and evaluated in the same manner as in Example 1 except that the weight ratio of each component was changed as shown in Table 1. Table 1 shows the weight ratio of each component and the evaluation results.

[0032] As described above, it is clear that in Comparative Examples 1 to 2 in which 1 part by weight of single-walled carbon nanotubes is added to a dispersant or a binder component, the conductivity is not much improved compared to Comparative Example 3 in which no single-walled carbon nanotubes are used, but in Examples 1 to 8 in which a dispersant and a binder component are used together, a higher conductivity can be achieved.

[0033] <Examples 9 to 16> As the binder component, a carbon nanotube dispersion was prepared in the same manner as in Example 3, except that poly(2-ethylhexyl acrylate) (PEHA) was used in Example 9, poly(butyl acrylate-isobutyl acrylate) (PBA / PIBA) was used in Example 10, poly(butyl acrylate) (PBA) was used in Examples 11 and 12, poly(ethyl acrylate-butyl acrylate) (PEA / PBA) was used in Example 13, poly(2-ethylhexyl acrylate-methoxypolyethylene glycol monoacrylate) (PEHA / PMOPEGA) was used in Example 14, and poly(butyl acrylate-methoxypolyethylene glycol monoacrylate) (PBA / PMOPEGA) was used in Examples 15 and 16. The physical properties (Mw, SP) of each acrylic resin and the evaluation results are shown in Table 2.

[0034] As described above, it was found that high conductivity can be achieved regardless of the type of acrylic resin as the binder component.

[0035] <Examples 17 to 23> As the dispersant, a carbon nanotube dispersion was prepared in the same manner as in Example 10, and the carbon nanotube dispersion was evaluated, except that polyoxyethylene-polyoxypropylene condensate (POEPOP, Mn=2000) was used in Example 17, polypropylene glycol (PPG) was used in Example 18, sorbitan trioleate (TOS) was used in Example 19, polyoxyethylene sorbitan trioleate (TOPOES) was used in Example 20, alkyl polyether phosphate (APEP) was used in Example 21, alkyl polyether carboxylic acid (APEC) was used in Example 22, and polyoxyalkylene amine (POAA) was used in Example 23. The physical properties (Mn) of each dispersant and the evaluation results are shown in Table 3.

[0036] As described above, it was found that high conductivity can be achieved regardless of the type of dispersant.

[0037] <Examples 24 to 26> A carbon nanotube dispersion was prepared and evaluated in the same manner as in Example 21 except that the weight ratio of each component was changed as shown in Table 4. Table 4 shows the weight ratio of each component and the evaluation results.

[0038] As described above, it was found that high conductivity can be achieved by using a dispersant (alkyl polyether phosphate (APEP)) in combination with a binder component.

[0039] This specification discloses at least the following inventions.

[0040] [1] A carbon nanotube dispersion comprising carbon nanotubes, a dispersant, and a binder component.

[0041] [2] The carbon nanotube dispersion according to [1], wherein the dispersant is an anionic surfactant.

[0042] [3] The carbon nanotube dispersion according to [2], wherein the anionic surfactant is a polyether phosphate ester or an alkyl polyether phosphate ester or a salt thereof.

[0043] [4] The carbon nanotube dispersion according to [1], wherein the dispersant is a cationic surfactant.

[0044] [5] The carbon nanotube dispersion according to [4], wherein the cationic surfactant is a polyetheramine or a salt thereof.

[0045] [6] The carbon nanotube dispersion according to [1], wherein the dispersant is a nonionic surfactant.

[0046] [7] The carbon nanotube dispersion according to [6], wherein the nonionic surfactant is a polyoxyalkylene.

[0047] [8] The carbon nanotube dispersion according to any one of [1] to [7], wherein the binder component is an acrylic resin.

[0048] [9] The carbon nanotube dispersion according to any one of [1] to [7], wherein the binder component is an epoxy resin.

[0049]

[10] The carbon nanotube dispersion according to any one of [1] to [7], wherein the binder component is polyethylene ether.

[0050]

[11] The carbon nanotube dispersion according to any one of [1] to

[10] , wherein the carbon nanotubes are single-walled carbon nanotubes.

[0051]

[12] The carbon nanotube dispersion according to any one of [1] to

[11] , wherein the content of the carbon nanotubes is 0.01 to 20% by weight.

[0052]

[13] The carbon nanotube dispersion according to any one of [1] to

[12] , wherein the weight ratio of the dispersant to the binder component (dispersant / binder component) is 1 / 99 to 99 / 1.

[0053]

[14] A conductive material comprising the carbon nanotube dispersion described in any one of [1] to

[13] .

Claims

1. A carbon nanotube dispersion, characterized in that: Contains carbon nanotubes, dispersants, and binder components.

2. The carbon nanotube dispersion according to claim 1, characterized in that The dispersant is an anionic surfactant.

3. The carbon nanotube dispersion according to claim 2, characterized in that The anionic surfactant is polyether phosphate or alkyl polyether phosphate or a salt thereof.

4. The carbon nanotube dispersion according to claim 1, characterized in that The dispersant is a cationic surfactant.

5. The carbon nanotube dispersion according to claim 4, characterized in that The cationic surfactant is polyetheramine or its salt.

6. The carbon nanotube dispersion according to claim 1, characterized in that The dispersant is a nonionic surfactant.

7. The carbon nanotube dispersion according to claim 6, characterized in that The nonionic surfactant is polyoxyalkylene.

8. The carbon nanotube dispersion according to claim 1, characterized in that: The adhesive component is acrylic resin.

9. The carbon nanotube dispersion according to claim 1, characterized in that: The adhesive component is epoxy resin.

10. The carbon nanotube dispersion according to claim 1, characterized in that: The adhesive component is polyvinyl ether.

11. The carbon nanotube dispersion according to claim 1, characterized in that: The carbon nanotubes are single-layer carbon nanotubes.

12. The carbon nanotube dispersion according to claim 1, characterized in that: The content of the carbon nanotubes is 0.01 to 20% by weight.

13. The carbon nanotube dispersion according to claim 1, characterized in that: The weight ratio of the dispersant to the binder component (dispersant / binder component) is 1 / 99 to 99 / 1.

14. A conductive material, characterized in that: A carbon nanotube dispersion comprising the carbon nanotube dispersion according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Dispersion and production method of the same, as well as composite body

    JP2021057271A